MODEL PENGEMBANGAN MASYARAKAT BERAGAMA - Athoilah aly najamudin; Emi Hidayati; Ginanjar Prastyanto (Department of Islamic Community Development, Faculty of Dakwah,Universitas Islam Ibrahimy Banyuwangi, 2023)
The development of religious communities is an interesting research area to study, this is because human behavior always has a relationship with the surrounding community. In practice, society makes religion a way of life. Community development is one of the instruments towards a harmonious community life order. However, recently, there have been many challenges in implementing the empowerment of religious communities, ranging from inter-religious conflicts to radical and conservative understandings of Islam. In this context, this paper finds a model for developing a religious community with the aim of strengthening and disseminating an understanding of community development in the space of a religious community. The approach in this study is to study literature or literature from various references obtained. This paper shows that there are 3 (three) models in the development of religious communities (1) the Medina community development model, (2) the ABCD community development model, (3) the people, centered, participatory community development model, (4) the inter-religious community development model.